Understanding the evolutionary dynamics of Monkeypox virus through less explored pathways - Alessandra Mistral De Pascali; Ludovica Ingletto; Martina Brandolini; Ettore Rocchi; Martina Tarozzi; Maria Elena Turba; Rita Casadio; Fabio Gentilini; Giulia Gatti; Laura Dionisi; Claudia Colosimo; Massimiliano Guerra; et al. (Scientific Reports)
Abstract Recent Monkeypox virus (MPXV) outbreaks in non-endemic regions have highlighted the need for genomic surveillance to support epidemiological investigations and monitor viral evolution. In this paper we present the results of genomic characterization and analyses of mechanisms of human adaptation, including APOBEC-style mutations, performed on 11 MPXV isolates, collected from May to September 2022, from Emilia-Romagna (Italy). Phylogenetic analysis confirmed all strains belonged to Clade IIb. Viruses from male patients were classified within lineage B (sub-lineages B.1, B.1.3, B.1.12), while a strain from a female patient was assigned to lineage A (A.2.3), with epidemiological links to Ghana. This represents the fourth detection of an A.2.3 strain of African origin outside the continent. Disruptions were identified in two genes: OPG176 (similar to VACV-Cop A46R), as reported in lineage A, and OPG023 (similar to VACV-Cop D7L), resulting in protein truncation that may suggest a possible pattern of human adaptation. These findings further enhance our understanding of MPXV Clade IIb diversity through characterization of a rarer variant giving insights from a less explored epidemiological pathway.